2016
DOI: 10.15171/jrip.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin II type 1 receptor blockade on kidney ischemia/reperfusion; a gender-related difference

Abstract: Background: Renal ischemia/reperfusion (I/R) injury may be related to activity of reninangiotensin system (RAS), which is gender-related. In this study, it was attempted to compare the effect of angiotensin II (Ang II) receptor type 1 (AT1R) blockade; losartan in I/R injury in male and female rats. Materials and Methods: Male and female Wistar rats were assigned as sham surgery, control I/R groups treated with vehicle, and case I/R groups treated with losartan (30 mg/kg). Vehicle and losartan were given 2 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…When it comes from ischemia/reperfusion the observations are not consistent. Studies conducted in Wistar rats have found that functional and structural injuries induced by ischemia/reperfusion are worsen in the male than female 43 46 , similar between female and male 47 , 48 , or even worsen in female than male rats 49 , 50 , and these results differ to that occurs in mice in which the females are more resistant to IR injury 39 . Using renal function (creatinine clearance and renal blood flow), and tubular injury markers (proteinuria, injured tubules %, and urinary excretion of Hsp72), we found, that after 24-h of renal bilateral ischemia, female and male rats displayed the same magnitude of IRI.…”
Section: Discussionmentioning
confidence: 93%
“…When it comes from ischemia/reperfusion the observations are not consistent. Studies conducted in Wistar rats have found that functional and structural injuries induced by ischemia/reperfusion are worsen in the male than female 43 46 , similar between female and male 47 , 48 , or even worsen in female than male rats 49 , 50 , and these results differ to that occurs in mice in which the females are more resistant to IR injury 39 . Using renal function (creatinine clearance and renal blood flow), and tubular injury markers (proteinuria, injured tubules %, and urinary excretion of Hsp72), we found, that after 24-h of renal bilateral ischemia, female and male rats displayed the same magnitude of IRI.…”
Section: Discussionmentioning
confidence: 93%
“…Some clinical and experimental animal studies have found evidence for the upregulation of RAS system in the progression of renal disease,[1011] and AT1R blockade may improve impaired kidney. [612] The effects of losartan through decreasing of inflammation, blood pressure, platelet activation and aggregation, and increasing of vasodilation and glomerular filtration rate (GFR) have been reported. [131415] In the present study, we showed the effects of losartan on renal function in 4/6 nephroctomized male and female rats, and the major findings indicated that losartan increased Cr clearance and UF in both genders; however, it was significant only in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…AT1R belongs to a family of seven transmembrane G protein-coupled receptors (GPCR) and regulate most of the physiological activities of Ang II in various kinds of target cells (Moslemi et al, 2016 ). AT1R plays a predominant role in the control of AngII-induced vascular functions.…”
Section: Structural Characteristics and Physiological Functions Of Bkmentioning
confidence: 99%